Novel Application of the Two‐Period Microtracer Approach to Determine Absolute Oral Bioavailability and Fraction Absorbed of Ertugliflozin. Issue 4 (25th March 2018) - Raje, Sangeeta; Callegari, Ernesto; Sahasrabudhe, Vaishali; Vaz, Alfin; Shi, Haihong; Fluhler, Eric; Woolf, Eric J.; Schildknegt, Klaas; Matschke, Kyle; Alvey, Christine; Zhou, Susan; Papadopoulos, Dimitris; et al.
Abstract: Ertugliflozin, a sodium glucose cotransporter‐2 inhibitor, is approved in the United States for treatment of type 2 diabetes mellitus. A novel two‐period study design with 14 C microtracer dosing in each period was used to determine absolute oral bioavailability (F) and fraction absorbed (Fa ) of ertugliflozin. Eight healthy adult men received 100‐μg i.v. 14 C‐ertugliflozin (400 nCi) dose 1 h after a 15‐mg oral unlabeled ertugliflozin dose (period 1), followed by 100 μg 14 C‐ertugliflozin orally along with 15 mg oral unlabeled ertugliflozin (period 2). Unlabeled ertugliflozin plasma concentrations were determined using high‐performance liquid‐chromatography tandem mass spectrometry (HPLC‐MS/MS). 14 C‐ertugliflozin plasma concentrations were determined using HPLC‐accelerator mass spectrometry (AMS) and 14 C urine concentrations were determined using AMS. F ((area under the curve (AUC)p.o. / 14 C‐AUCi.v. )*( 14 C‐Dosei.v. /Dosep.o. )) and Fa (( 14 C_Total_Urinep.o. / 14 C_Total_Urinei.v. )* ( 14 C‐Dosei.v. / 14 C‐Dosep.o. )) were estimated. Estimates of F and Fa were 105% and 111%, respectively. Oral absorption of ertugliflozin was complete under fasted conditions and F was ∼100%. Ertugliflozin was well tolerated.